One-Step/One-Pot Decoration of Oxide Microparticleswith Silver Nanoparticles - Macchione, Micaela Alejandra (2014)
Hypothesis:Heterogeneous nucleation of silver oxide (Ag2O) onto oxide microparticles (OMPs) followedby spontaneous thermal decomposition produce nanostructures made of OMPs decorated with silvernanoparticles (OMP|AgNPs).Experiments:Colloidal chemistry methods have been used to produce the decoration of OMPs with silvernanoparticles (AgNPs), by carrying out the Ag2O precipitation/thermal decomposition. The process is dri-ven in water enriched acetone medium containing NaOH, NH3, AgNO3and SiO2MPs as substrate. Opticaland morphological properties of OMP|AgNPs were characterized by using STEM, EDS, HRTEM and Ramanspectroscopy.Findings:A new synthetic method to decorate OMPs (TiO2, SiO2) with metallic AgNPs in a single step/singlepot reaction is proven effective to produce OMP|AgNPs either in aqueous or water enriched media.